DEVELOPING EDUCATIONAL VALUE TROUGH KITAB TA’LIM MUTA’ALIM FOR CHILDREN IN MUSHOLLA NURUL FUR’QAN, BILLAPORA TIMUR VILLAGE - Himmah, Atikatul; Setiyawan, Arisandi; Nazalatus Sa’adiyah , Eva (Proceedings of Annual Conference on Community Engagement, 2024)
The COVID-19 has resulted in schools shut all across the world. Globally, over 1.2 billion children are out of the class. As a result, education has changed dramatically, with the distinctive rise of e- learning on digital platform.Students are getting closer with gatget todays. Gadget replace everything in children life. They used to study and play trough their hand phone. This condition seem to be matter and make parents worry a lot in teaching a good moral ( akhlak .) Adaptation on children behaviour need to be tought again with the best education book. Musholla is one of the best place for children to build their good character. In musholla students learn to read a holy alqur’an and also kitab ta’lim. This. This study aimed to (1) describe educational value through kitab ta’lim muta’alim for children in musholla nurul fur’qan, billapora timur village after pandemic. On the next phase, character education should be implemented in society, government agency, society organization, non-governmental organization, company and other group society.